Kirke-klokken og andre digtninger fra 1845 - Toldberg, Helge (Grundtvig-studier, 1963)
Kirke-Klokken (“ The Church Bell” ) and Other Poetical Works from 1845. By Helge Toldberg. Revised by Dr. Noelle Davies. Kirke-Klokken, a poem of 10 stanzas, first appeared on October 19th, 1845, in the periodical “ Dansk Kirketidende” (Danish Ecclesiastical Times), but not until 1953 did this original version enter the Danish Hymnal. For exactly 100 years the version in normal use, particularly at funerals, was an abridged one of 6 stanzas (beginning with the second), first published by Grundtvig’s son-inlaw. The latter, “ Sacred bell, ’twas not for teeming city” , was translated into English by R. P. Keigwin (v. his anthology “ In Denmark I was born” , 1948, P. 37); it is well done, but it is a pity that he has not preserved the peculiar rhyme-scheme of the original, which left the second and fourth lines of each stanza unrhymed. When Svend Grundtvig adapted Kirke-Klokken for the standard edition of his father’s poetical works, he was unaware of extant MSS.; but during a discussion of the poem in 1897 the draft as well as a neat copy turned up, the former being of immense interest; and quite recently another neat copy, with which Grundtvig had presented his daughter, has been discovered. It is of earlier date than the one discovered in 1897, and various marks on it prove it to have been used for the abridgment by her husband. V. facsimiles of the latter and the draft facing PP. 16-17. The draft displays two stages of the poem. The former is of two stanzas only, and is rhymed abab, whereas the latter is rhymed abac, and also in other respects resembles the finished poem, but for the 9th stanza being absent and the 8th being added underneath. But moreover the two stages differ in scope, the former describing the general appeal of the bell, the latter its appeal to Grundtvig himself. The discussion in 1897 was started by Otto Møller, a clergyman of some renown, who was absolutely convinced that the poem was older than usually supposed, written under the impression of revisiting Udby, Grundtvig’s native village, in May 1844. To be sure, stanzas 4 and 5 describe the effect on him in childhood of the chimes at Christmas and Easter, and according to the 8th stanza, added underneath, he now feels homeless in the country. But all this may be due to memory, and does not exclude the possibility that the poem as a whole originates from the summer or autum of 1845, when he was a resident at “ Bakkehuset” in the parish of Frederiksberg, then a peaceful village outside Copenhagen. Its beautiful parish church might very well suggest one of the chief themes of the poem: that the church bell appeals to the village much more than to the capital. The discussion was brought to an end by a statement of the widow of the author Frederik Barfod, who remembered visiting Grundtvig at “ Bakkehuset55, his pleasure at listening to the curfew, and his own remarks on the poem composed just then. Exact knowledge of the date of origin is of some importance, because Kirke-Klokken may very well be a response to Klokken, a tale by Hans Christian Andersen (v. R. P. Keigwin5s translation, “ The Bell55, in Vol. I l l of Andersen^ “ Fairy Tales55, Odense 1958), and two poems by other authors also first published in 1845. A clue to one of these possible connections is a tradition quoted and ridiculed by Otto Møller: that Grundtvig composed Kirke- Klokken on the city wall of Copenhagen and handed it over to his daughter, who kept it in a drawer, where it was found by her husband 20 years later and only then published. As a matter of fact, but for the legend about the city wall, and 20 (in Danish: tyve) as a mishearing for 7 (syv), the tradition is correct, and the city wall makes sense, too, if combined with another peculiar statement: that the poem was composed on the eve of Store Bededag (“ Great Praying-Day55, a Danish holiday 4 weeks after Good Friday). It must be a reference to Paa Volden store Bededag (“ On the City Wall on S.B.55), a poem by Henrik Hertz (1798-1870) describing a nine-year-old girl's everyday questions to the bells and their constant answer: “ Not at all!55 Verbal similarities as well as Grundtvig5s general dislike of abuse of holy symbols suggest that he may have written Kirke-Klokken in refutation of Hertz5 poem. Though it was published two months after Kirke-Klokken, so that Grundtvig cannot have read it, he may very well have heard it quoted in full or in part, and the two first stanzas would suffice. It is even possible to suggest a channel. A few days after composing his poem, in October 1844, Hertz presented Johanne Louise Heiberg, the famous actress, with a copy, and an intimate friend of the Heiberg family's, H. L. Martensen, later Bishop of Copenhagen, was just then on a committee with Grundtvig, preparing a new Danish hymnal, where they were at variance on matters of style and Martensen5s attempts at correcting “vulgarities55 in Grundtvig5s hymns. Though no absolute proof is available, it seems a sound working hypothesis that Martensen may have quoted, say, the two first stanzas of Hertz5 poem as an example of better taste than Grundtvig5s. As for The Bell by Hans Andersen, which was published as early as May 1845, we have no evidence of Grundtvig5s being concerned with it, but the theory of a connection would immensely facilitate the interpretation of the first version in the draft, and provide a welcome explanation of the “precious metals55 which according to Grundtvig are surpassed by the church bell. Two such metals occur in Andersen5s tale, a small bell that satisfies formalists of no profound inspiration, and a big one “ in the great cathedral of nature and poetry55 found only by the ardent adorers, the prince and the poor boy, symbolizing H. C. Ørsted (famous physicist and philosopher) and Andersen. But because of Grundtvig5s and Andersen5s mutual dislike and disapproval of each other's attitude towards religion, only an influence from without could have directed Grundtvig5s attention to the tale. It might have been the Baroness Stampe at Nysø, where Andersen copied out The Bell after it had appeared in a children^ magazine, or her daughter Elise, who was a favourite of both poets, and according to Andersen collected proverbs and verses for Grundtvig. It is, however, within probability that the latter may have seen some of the monthly issues of the magazine, which was a real success, nor is it unlikely that he wrote his ninth stanza as a last-minute protest against a goblin’s Christmas carol in a tale on Andersen’s pattern in the September issue by Julius Gerson, a minor poet (1811-94), one of the editors of the magazine. The suggestions that it may include polemics against the contents or religious outlook of contemporary poetical works does not imply any revision of the idea of Kirke-Klokken as a personal poem, but extends its range from a Christian poet’s confessions to a statement of Christianity as the proper concept of human life, amplified by the changing associations conveyed by the pealing bells. This does not preclude passages of a strictly private nature, above all the 8th stanza on Grundtvig’s homelessness in the country in his old age, composed a little later than the rest, so that the poem should be regarded equally as a subjective hymn on the Message of the Church and as his own Christian testament.